SMEs and Sustainable Practices: Identifying Key Factors from Spanish Evidence - José Antonio Clemente-Almendros; Marcelo Vallejo García; María Blanco-Hernández (SAGE Open)
Understanding the complex process of adopting sustainable practices in small and medium-sized enterprises (SMEs) is a challenging but necessary task, given the prevalence of these companies and the institutional pressure to move towards sustainability. Using a representative database of Spanish SMEs, we aim to show which factors help SMEs to embrace sustainability. The results show that organizational agility, internationalization, the academic background of the manager and size all exert a positive effect on sustainable practices. Our study provides meaningful insights to help SMEs overcome some of their deficiencies in sustainability commitment and the adoption of sustainable practices, which can be extended to other countries and broader areas such the European Union.